Nitrolancea hollandica gen. nov., sp. nov., a chemolithoautotrophic nitrite-oxidizing bacterium isolated from a bioreactor belonging to the phylum Chloroflexi - Sorokin, Dimitry Y; Vejmelkova, Dana; Lücker, Sebastian; Streshinskaya, Galina M; Rijpstra, W Irene C; Sinninghe Damsté, Jaap S; Kleerbezem, Robbert; van Loosdrecht, Mark; Muyzer, Gerard; Daims, Holger (International journal of systematic and evolutionary microbiology, 2014)
A novel nitrite-oxidizing bacterium (NOB), strain Lb(T), was isolated from a nitrifying bioreactor with a high loading of ammonium bicarbonate in a mineral medium with nitrite as the energy source. The cells were oval (lancet-shaped) rods with pointed edges, non-motile, Gram-positive (by staining and from the cell wall structure) and non-spore-forming. Strain Lb(T) was an obligately aerobic, chemolitoautotrophic NOB, utilizing nitrite or formate as the energy source and CO2 as the carbon source. Ammonium served as the only source of assimilated nitrogen. Growth with nitrite was optimal at pH 6.8-7.5 and at 40 °C (maximum 46 °C). The membrane lipids consisted of C20 alkyl 1,2-diols with the dominant fatty acids being 10MeC18 and C(18 : 1)ω9. The peptidoglycan lacked meso-DAP but contained ornithine and lysine. The dominant lipoquinone was MK-8. Phylogenetic analyses of the 16s rRNA gene sequence placed strain Lb(T) into the class Thermomicrobia of the phylum Chloroflexi with Sphaerobacter thermophilus as the closest relative. On the basis of physiological and phylogenetic data, it is proposed that strain Lb(T) represents a novel species of a new genus, with the suggested name Nitrolancea hollandica gen. nov., sp. nov. The type strain of the type species is Lb(T) ( = DSM 23161(T) = UNIQEM U798(T)).
Keywords: zastoupení bazí; RNA ribozomální 16S; Nizozemsko; Chemoautotrophic Growth; Nitrification; nitrifikace; chemoautotrofní růst; Nitrites; Netherlands; DNA bakterií; Oxidation-Reduction; bioreaktory; Chloroflexi; Peptidoglycan; dusitany; vitamin K 2; RNA, Ribosomal, 16S; fylogeneze; DNA, Bacterial; mastné kyseliny; Sequence Analysis, DNA; peptidoglykan; sekvenční analýza DNA; Base Composition; oxidace-redukce; molekulární sekvence - údaje; Fatty Acids; Vitamin K 2; Molecular Sequence Data; Bioreactors; Phylogeny